The change of metal pollution in the water and sediment of the Bart?n River in rainy and dry seasons - Güneş, Gülten; Güneş, Gülten (Korean Soc Environmental Engineers - Ksee, 2022)
In this study, it was aimed to determine the heavy metal pollution and the factors causing this pollution in the water and sediment of the samples collected from 4 different points during rainy and dry periods were investigated. It has been determined that both natural sources (soil erosion) and anthropogenic sources (runoff in urban and agricultural areas) affect metal concentrations in water and sediment during the rainy period. Heavy metal accumulation was less at the point with the least water depth (??? 2 m). Higher concentrations were determined at the point where soil transport was highest during the rainy period. Since EF values of As, Pb, Zn and Li were greater than two in both periods, it was determined that they were affected by anthropogenic sources (wastewater discharges, agricultural and urban activities). EF values less than one showed that Co, Cr, Ba, Ni, Mn were related to lithogenic actions and riverbank runoff. Non-carcinogenic effects caused by metals did not pose a risk to adults and children.
Keywords: Ecological Risk; Heavy Metal; Multi Metal Indices; Sediment Quality